Usability and Acceptance of EduPetualang: A SUS Study in Bandung Elementary Schools - E Silmi Kaaffah; Yunus Abidin; Dede Tri Kurniawan (Journal of Future Education, 2024)
This study aims to evaluate the usability level of the EduPetualang learning platform using the System Usability Scale (SUS). Usability is assessed through four main aspects: effectiveness, efficiency, satisfaction, and user control. The research involved 112 teacher respondents who used the platform in an educational context. Data were collected using a ten-item SUS questionnaire and analyzed quantitatively. The findings indicate that users perceived the platform as easy to use, well-integrated, and satisfactory for achieving learning goals. Overall, EduPetualang was evaluated to have excellent usability according to standardized SUS benchmarks. The results suggest that the platform supports learning activities effectively and is well-received by users, particularly educators. The study concludes that EduPetualang is suitable for implementation in classroom settings and provides recommendations for improving system features to further enhance user experience